PID ROBUST Hinf INTEGRAL-BACKSTEPPING CONTROL WITH OPTIMAL CONTROL STRATEGY FOR AUTOMATED PEOPLE MOVERS (APM) - Elbert Suryana, Lucas
Nowadays, train signaling system technology in Indonesia is experiencing rapid development with the construction of rail-based public transport infrastructure for urban areas, known as urban transit. This signaling system technology is known as Communication-Based Train Control (CBTC). There is three urban transit construction in Indonesia. They are Light Rail Transit (LRT) which connects Jakarta-Bogor-Depok-Bekasi, Mass Rapid Transit (MRT) in the middle of Jakarta, and Automated People Movers (APM) which connects terminals 1,2 and 3 at Soekarno-Hatta International Airport, Tangerang.